ANALISIS KERUSAKAN DAN PERBAIKAN PERKERASAN BETON SEMEN PADA JALAN LINGKAR TIMUR - Duha, Fitrahmansyah; Firdaus, Firdaus (Ensiklopedia of Journal, 2025)
This study analyzes the damage and repair of rigid pavement on the East Ring Road of Prabumulih. This road serves as a crucial infrastructure supporting mobility and regional economic growth. The primary objective of this research is to identify the types and causes of damage to the rigid pavement and recommend appropriate repair methods to enhance the road’s quality and service life. The research was conducted through direct field observations and data collection from relevant agencies. The findings indicate that the most dominant types of damage include longitudinal cracks, punch-outs, and potholes. The main contributing factors to these damages are excessive vehicle loads (overloading), extreme weather conditions, and inconsistencies in road planning and construction. To address these issues, several repair methods were proposed, including Partial Depth Repair (PDR) and concrete injection, both of which have proven effective in restoring road structure without requiring complete reconstruction. This study emphasizes the importance of thorough planning and strict adherence to technical standards in road construction and maintenance. Additionally, stricter regulations on overloaded vehicles should be enforced to prevent further damage. By implementing appropriate repair methods and effective maintenance policies, the quality and durability of the East Ring Road of Prabumulih can be continuously improved to support mobility and ensure road user safety.Keywords: Pavement damage analysis, rigid pavement, road repair, concrete injection, road maintenance